094 Home mechanical ventilation (HMV) in motor neurone disease: a 12 year single centre cohort study. Issue 6 (27th May 2022) - Kaltsakas, George; Ramsay, Michelle; Howard, Leo; Sheridan, Shauna; Murphy, Patrick; Marino, Phillip; Hart, Nick; Howard, Robin
Abstract : HMV support for patients living with motor neuron disease MND is recommended by NICE to improve quality of life and survival. Although there are intermediate term outcome data, long-term data are sparse. From 2007 to 2019, 413 patients (246 male) received HMV; 310 have died (75.0%). Age at onset was 61.4 ± 12.4 years. The duration between onset of symptoms and diagnosis was 13 months (0–104) and between onset of symptoms and referral was 29 months (0–300). At presentation, 37% patients had established res- piratory failure with a further 13% exhibiting incapacitating breathlessness. Survival was 11.9 ± 18.5 months after commencing HMV although the duration of HMV support for those still alive was 26.6 ± 30.5 months. 9.0% received long-term tracheostomy; 53% had gastrostomy feeding tubes and 25.7% cough assist device. These data show a delay both in establishing a definitive diagnosis of MND and in referring for specialist support. Delaying referral until severe respiratory compromise has developed may reduce the sympto- matic benefits of NIV. Prolonged survival with HMV support is possible but early intervention is essential to optimise clinical management. The data and clinical experience serve to emphasise the importance of early referral for specialist respiratory assessment and management. robinhoward@nhs.net